Intervention programs in educational psychology: bridging research and practice - Gomes-Koban, Clara; Calet, Nuria; Defior, Sylvia (Anales de Psicología / Annals of Psychology, 2019)
The term evidence-based intervention has been increasingly used in educational research. Calls for the use of intervention programs based on supportive empirical evidence rely in the recognition that the likelihood of achieving positive results when implementing such programs increases. Nevertheless, the gap between research and practice remains also in Spanish-speaking countries. Using examples from the area of reading research, this work aims at promoting the reflection and discussion about the relationship between scientific evidence and school practice, particularly in the context of Spanish-speaking countries. On the one side, there is the importance of generating evidence through the design of high-quality studies based on both sound theoretical background and high methodological standards. On the other side, there is the value of professional experience gathered by the teachers in very diverse school realities. How can we build a bridge to connect these two indispensable parts in order to be able to better serve the populations of interest? We defend the need of developing a sustainable collaborative system between the research community and the educational centers that enables continuous exchange and reciprocal support in longer lasting relationships.